Chemopreventive Effect on Human Colon Adenocarcinoma Cells of Styrylquinolines: Synthesis, Cytotoxicity, Proapoptotic Effect and Molecular Docking Analysis - Vanesa Bedoya-Betancur; Elizabeth Correa; Juan Pablo Rendón; Andrés F. Yepes-Pérez; Wilson Cardona-Galeano; Tonny W. Naranjo (Molecules, 2022)
Seven styrylquinolines were synthesized in this study. Two of these styrylquinolines are new and were elucidated by spectroscopic analysis. The chemopreventive potential of these compounds was evaluated against SW480 human colon adenocarcinoma cells, its metastatic derivative SW620, and normal cells (HaCaT). According to the results, compounds 3a and 3d showed antiproliferative activity in SW480 and SW620 cells, but their effect seemed to be caused by different mechanisms of action. Compound 3a induced apoptosis independent of ROS production, as evidenced by increased levels of caspase 3, and had an immunomodulatory effect, positively regulating the production of different immunological markers in malignant cell lines. In contrast, compound 3d generated a pro-oxidant response and inhibited the growth of cancer cells, probably by another type of cell death other than apoptosis. Molecular docking studies indicated that the most active compound, 3a, could efficiently bind to the proapoptotic human caspases-3 protein, a result that could provide valuable information on the biochemical mechanism for the in vitro cytotoxic response of this compound in SW620 colon carcinoma cell lines. The obtained results suggest that these compounds have chemopreventive potential against CRC, but more studies should be carried out to elucidate the molecular mechanisms of action of each of them in depth.